RANCANG BANGUN SISTEM INFORMASI RENCANA DAN PEMUSNAHAN LIMBAH (E-WASTE) BERBASIS WEB (STUDI KASUS DI FARMASI) - Muhammad Noval Riswandha; Ahmad Syaifudin (SPIRIT, 2020)
Abstract: In handling waste, it is important to know that there are types of waste that turn out to be very threatening to the environment and human health. This type of waste is commonly referred to as B3 waste. A pharmaceutical company is one company that produces B3 waste in its production process that requires proper handling in the process of destroying waste so as not to endanger the surrounding humans. The process of transaction and documentation in pharmacy which the author makes research using conventional methods which sometimes causes problems in reading different people's handwriting and file storage that is increasingly piling up. With advances in developments in information technology expected to solve problems in the process of eradicating the waste, the authors designed a system that can be used as an inter-building transaction and provide digital approval to support efficiency and transportation in conventional processes.. Kata Kunci: approval system, e-waste